Film Morphology of High Efficiency Solution‐Processed Small‐Molecule Solar Cells. (22nd May 2013) - Love, John A.; Proctor, Christopher M.; Liu, Jianhua; Takacs, Christopher J.; Sharenko, Alexander; van der Poll, Thomas S.; Heeger, Alan J.; Bazan, Guillermo C.; Nguyen, Thuc‐Quyen
<x xml:space="preserve">Abstract</x> Morphological control over the bulk heterojunction (BHJ) microstructure of a small‐molecule photovoltaic system is demonstrated using thermal treatment and solvent additives. Single crystal X‐ray diffraction and transmission electron microscopy are utilized to investigate solid‐state interactions and the BHJ morphology. Domain size and molecular order are crucial to achieving the 7.0% power conversion efficiency and over 90% internal quantum efficiency exhibited under optimized conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>